Conferences of Minister Presidents of the German States in 1948—1949 and Their Political Significance - I. D. Popov (Научный диалог)
The activity and political significance of the conferences of the Minister Presidents of the German states during the years of the institutionalization of the Federal Republic of Germany (1948—1949) are considered. It is concluded that in the absence of a number of significant central authorities, it was the conferences of the heads of state governments that played a coordinating role to fill them up on the German side. It is noted that the Minister Presidents also served as a converging point between the allies, the regional elite, political parties and bizone authorities. It is shown that various formats of work of heads of state governments at the interzonal level allowed them to take part in the discussion of almost all key problems of the western zones of occupation. It is emphasized that the two-zone meetings of the Minister Presidents with the military governors and the three-zone conferences of the Minister Presidents themselves, which in fact became the main instruments for reaching political compromises, had a particular impact. It is pointed out that this was especially clearly manifested during the discussion of the “Frankfurt Documents”. It is concluded that, at the same time, the dependence on the military administrations of the allies, the party elite and bizone authorities at the same time did not allow these conferences to evolve into something more than a platform for building consensus, and thereby pursue a full-fledged independent policy.